¬نکاح و طلاق سے متعلق حضرت عبداللہ ابن عباس ؓکے فقہی اقوال کا تحقیقی جائز: Research Analysis of Legal Maxims and Edicts of Hazrat Abdullah bin Abbas R.A Regarding Marriages and Divorce (Al-Aasar, 2025)
Hazrat Abdullah Bin Abbas R.A is the maternal cousin of Khalid Bin Waleed (R.A.) paternal cousin and prominent companion of Holy Prophet Muhammad ﷺ. Holy Prophet Muhammad ﷺ prayed him as 'O Allah, teach him wisdom and the (correct) interpretation of the Book. This Article talks about Teaching circle and dignified status of Abdullah bin Abbas R.A in the field of Islamic Jurisprudence and Legal Maxims. He was Interpreter of Quran, Muhadith, leading judge and jurist consult in Madinah and has His Legal Maxims and edicts are constituted on 20 volumes. This Article talks about Legal issues regarding Marriage and divorce in sight of Islam. Abdullah Bin Abbas R.A point of view are vital importance. This Article concerns many important issues likewise Marriages with the people of books, Marriage in wearing Hajj Ahraam, Marriages with non-Mahram, and important terms and conditions before marriages. Even this article covers those issues which were practised before advent of Islam in Arabian Peninsula likewise polygamy, Zihar, Halala and many such kind of marriages and divorce issues on that specific era. These issues are of vital importance in Islamic Martial lives which we should know, and we can adopt to get Straight Islamic path and true guidance.